1995
DOI: 10.1007/bf01438856
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the thermodynamic properties of complex polyatomic hydrogen bonding fluids

Abstract: A new theory for intramolecular hydrogen bonding of flexible hard chain molecules in the absence of intermolecular association is presented. The theory predicts tile change in thermodynamic properties due to intramolecular association and the fraction of nonbonded chains. Comparisons with molecular simulation results are presented to demonstrate tile accuracy of tile theory. By considering the limit of complete association, an accurate equation of state of cyclic molecules is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 25 publications
(26 reference statements)
2
9
0
Order By: Relevance
“…3 we see that intramolecular association is favored at low temperatures ͑or high association energies͒. In our previous paper 20 we developed an equation of state for ring molecules. Ring molecules have a compressibility factor less than that of monomer chain molecules with the same number of segments but greater than that for intermolecularly bonded dimers.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…3 we see that intramolecular association is favored at low temperatures ͑or high association energies͒. In our previous paper 20 we developed an equation of state for ring molecules. Ring molecules have a compressibility factor less than that of monomer chain molecules with the same number of segments but greater than that for intermolecularly bonded dimers.…”
Section: Resultsmentioning
confidence: 89%
“…20 It was shown that the form of the Helmholtz free energy could be derived by considering the low density limit. 20 This is based, in part, on the observation by Andersen that the form of the combinatorial terms in cluster expansions of an associated fluid is the same regardless of the density. 24 Thus the form of the expression for the Helmholtz free energy can be easily determined at low density.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations